2023
DOI: 10.3390/antiox12081625
|View full text |Cite
|
Sign up to set email alerts
|

Ozonated Sunflower Oil Exerted Potent Anti-Inflammatory Activities with Enhanced Wound Healing and Tissue Regeneration Abilities against Acute Toxicity of Carboxymethyllysine in Zebrafish with Improved Blood Lipid Profile

Kyung-Hyun Cho,
Ji-Eun Kim,
Ashutosh Bahuguna
et al.

Abstract: Ozonated sunflower oil (OSO) is an established therapeutic agent and nutraceutical harboring various therapeutic values, including antiallergic, derma-protective, and broad-spectrum antimicrobial activity. Conversely, the medicinal aspects of OSO for wound healing, tissue regeneration, and treatment of inflammation in dyslipidemia have yet to be fully elucidated. Herein, a comparative effect of OSO and sunflower oil (SO) was investigated to heal cutaneous wound and tissue regeneration of zebrafish impediment b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 57 publications
(88 reference statements)
0
8
0
Order By: Relevance
“…Numerous studies have defined the varied therapeutic potential of ozone [26,27]. In our recent studies, we observed OSO as possessing antimicrobial [8], antioxidant, anti-inflammatory [9,10], and wound-healing activity [10]. Extending our earlier finding herein, we have evaluated the impact of prolonged (2 years) consumption of OSO on zebrafish survivability, body weight, liver, kidney, testis, ovary, and age-associated parameters to ascertain whether OSO is toxic or non-toxic when included in the diet.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Numerous studies have defined the varied therapeutic potential of ozone [26,27]. In our recent studies, we observed OSO as possessing antimicrobial [8], antioxidant, anti-inflammatory [9,10], and wound-healing activity [10]. Extending our earlier finding herein, we have evaluated the impact of prolonged (2 years) consumption of OSO on zebrafish survivability, body weight, liver, kidney, testis, ovary, and age-associated parameters to ascertain whether OSO is toxic or non-toxic when included in the diet.…”
Section: Discussionmentioning
confidence: 87%
“…Among the different ozonated oils, SO has been greatly acknowledged for its antimicrobial [8], anti-inflammatory, antioxidant [8,9], and wound-healing role [10,11]. As an antioxidant, ozonated SO (OSO) proved efficient in upregulating cellular antioxidants (superoxide dismutase) and reduced thiobarbituric acid reactive substances (TBARS) in the gastric mucosa of rats [12].…”
Section: Introductionmentioning
confidence: 99%
“…For the histological analysis, the tissue was dehydrated using ethanol and embedded in paraffin wax following tissue sectioning (7 μm thick) using microtome (Leica, CM1510s, Heidelberg, Germany). The tissue sections from the liver, ovary, and testis were processed for hematoxylin and eosin staining (H&E) [ 48 , 49 ] to evaluate the morphological changes.…”
Section: Methodsmentioning
confidence: 99%
“…The wounded area of the zebrafish was persistently monitored at 0, 2, 4, 6, 24, and 48 h after being stained with methylene blue as an earlier adopted method [21]. Briefly, at the respective time point, zebrafish were anesthetized by drenching into 0.1% of 2-phenoxyethanol and the subsequent addition of methylene blue (0.1% w/v, final 2 µL) at the wounded site.…”
Section: Visual Observation Of Wound Healingmentioning
confidence: 99%
“…The use of zebrafish embryos is advantageous due to their external development and optical transparency through their developmental stages. These attributes make zebrafish and their embryos a suitable animal model for various studies, such as the screening of antioxidants [20], wound healing [21], and tissue regeneration [22].…”
Section: Introductionmentioning
confidence: 99%